The biology and management considerations of abundant large cyprinids in Lake le Roux, Orange River, South Africa - Tómasson, Tumi (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1983)
The biology of three large cyprinid fishes, Barbus holubi, B. kimberleyensis and Labeo capensis, was studied in a large turbid man-made lake on the Orange River, South Africa. The influence of environmental fluctuations on population dynamics was examined in relation to biological adaptations. On this basis inferences were made about the effect exploitation would have on the populations, and management alternatives were considered. Lake Ie Roux is situated in a semi- arid area, downstream from another large reservoir, Lake Verwoerd. In the pristine river, flooding is seasonal, and floodwaters carry a heavy silt load. Lake Verwoerd acts as a silt-trap and changes in turbidity in Lake Ie Roux (Secchi disc readings range from 15 to 160 cm) are influenced by hydrological management and are not necessarily seasonal. Water temperatures in the regulated river connecting the two lakes depend on the pattern of water release, and fluctuations in Iake levels depend on management practices. Reproduction was studied by examination of gonads and from the distribution of newly hatched juveniles. Age and growth was interpreted from the reading of scales and otoliths. Relative year class strength, dispersal and mortality were monitored using catch data from a regular, standardized gillnetting survey. The Barbus species spawn in the regulated river in spring or summer. Spawning is coordinated for a large part of the population and B. holubi spawn four to six weeks earlier than B. kimberleyensis. The juveniles are 'initially found along the shoreline, but later move into the pelagic zone and disperse throughout the lake. Year class strength is dependent on time of spawning and a late spawning results in a poor year class. For this reason, year class strength of B. kimberleyensis is generally poor, but there is a greater variation in year class strength of B. holubi, which is the dominant large Barbus. The two Barbus species exploit the pelagic zone, visually predating on zooplankton. When turbidity increases large scale mortalities occur, especially in B. holubi. Mortalities more than compensate for the reduction in carrying capacity, and the size of the reduced population may be inversely related to initial abundance. Growth rate is similarly affected by turbidity and density, and size at sexual maturity in B. holubi is reduced when growing conditions deteriorate. Labeo capensis do not form a homogenous population in Lake le Roux. Spawning occurs throughout the lake, but is erratic, probably depending on local rainfall. At each locality, more than one spawning may occur during spring and summer because of temporal variation in gonadal development. Juvenile survival appears to be mainly dependent on water level fluctuations, and strong year classes were formed when the lake was filling during the first two years. Subsequent year classes were weak. Subadult and adult B. capensis are herbivorous and depend on autochthonous production for food. They are relatively sedentary, but when turbidity increases fish smaller than 200 mm disperse, probably in response to food shortages. Mortality rates may be accelerated but mortalities are not as high as in B. holubi. The growth rate of B. capensis is variable and depends on turbidity and population density. Size at sexual maturity remained relatively constant during the study period. B. holubi has a relatively fixed reproduction cycle in Lake le Roux and exploitation is likely to dampen fluctuations in population density. Population growth and stability could be further promoted through hydrological management. B. kimberleyensis does not represent an exploitable population in Lake le Roux, although the large size obtained by this species (>3 kg) may be an attraction to anglers. B. capensis does not appear to have the potential to withstand sustained exploitation because of its erratic and generally poor reproductive success. However, the species is long-lived and can sustain relatively high densities under harsh conditions because of its relatively low mortality rates. It was concluded that harvesting of B. holubi must be flexible to promote maximum benefits to commercial and recreational fisheries, but B. capensis which is not an angling species, should chiefly be exploited when catches of B. holubi are poor, but left to recover in between. An alternative management strategy would be to commercially exploit the fish populations of several reservoirs. A monitoring programme could be established to decide when each reservoir is to be exploited to see to the interests of commercial and recreational fishing alike.
Keywords: Barbus; Labeo; Cyprinidae; Freshwater fishes -- South Africa